2019
DOI: 10.1039/c9nj02131k
|View full text |Cite
|
Sign up to set email alerts
|

Study of dispersion mechanisms of modified SiC powder: electrostatic repulsion and steric hindrance mechanism

Abstract: Surface modification technology was used to increase the dispersion of SiC powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The results showed that the addition of alumina and silica greatly improves the hardness of the material, which signi cantly enhances the cutting resistance of the fabric. A large number of studies have found that the surface treatment [20], mass fraction [21], size [22], and distribution [23,24] of IP will also affect the physical and mechanical properties of epoxy resin composites [25]. Among them, the dispersion of IP in the resin directly determines the physical and mechanical properties of the composites to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the addition of alumina and silica greatly improves the hardness of the material, which signi cantly enhances the cutting resistance of the fabric. A large number of studies have found that the surface treatment [20], mass fraction [21], size [22], and distribution [23,24] of IP will also affect the physical and mechanical properties of epoxy resin composites [25]. Among them, the dispersion of IP in the resin directly determines the physical and mechanical properties of the composites to a great extent.…”
Section: Introductionmentioning
confidence: 99%